PERANCANGAN KAMPUNG VERTIKAL DI DESA MURUNG KENANGA KABUPATEN BANJAR - Rusbandi Rusbandi; Dahliani Dahliani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The design of a vertical village in Murung Kenanga Village is a village design that is arranged upward with the aim of structuring slum areas, as well as efforts to overcome population density while still paying attention to the socio-culture of the people of Murung Kenanga Village. In an effort to pay attention to the socio-culture of the people of Murung Kenanga Village, the concept of character is used in designing a vertical village with a contextual approach. The contextual approach is carried out with the context of the site and cultural context. With the approach taken, it is hoped that it can bring the character of life of Murung Kenanga Village residents to the design of a vertical village in overcoming slum areas without giving significant changes to the lives of residents of origin in Murung Kenanga Village